PROBLEMS AND PERSPECTIVES OF MASS OPINION POLLS - Volianska, Olena (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2023)
In the twenty-first century, there is a significant crisis in electoral procedures, which is manifested in a decline in confidence in them. It coincided with a crisis in the survey technology of public opinion research, which is manifested in a decrease in efficiency, an increase in the number of refusals, a systematic error of representativeness and dependence of results on the wording of questions. The first crisis plays into the hands of populist strategies, as those who refused to participate in the survey are not included in the sample, and the second crisis requires the development of new ways to extract and process information about individual behavior, such as the analysis of algorithms, statistics of Internet sites, and big data analysis. The purpose of this article is to answer the question of what the prospects for the development of public opinion may be in light of the growing problems of representativeness.